Titanium alloy fastener self-repairing nano molybdenum disulfide lubricating coating and preparation method thereof

CN122978792APending Publication Date: 2026-10-27BEIJING INST OF ASTRONAUTICAL SYST ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611111182.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,传统纳米二硫化钼涂层存在三大核心缺陷,无法满足长期极端环境的服役要求:一是界面结合力不足,钛合金表面易形成致密的TiO2钝化层,导致传统涂层与基体结合能低,在剪切应力作用下易剥离、脱落;二是化学稳定性差,太空极端环境中的原子氧、紫外线辐照、高低温循环会加速MoS2氧化、降解,潮湿环境下生成无润滑性能的MoO3产物,这是导致涂层长期润滑失效的关键原因;三是无自修复能力,涂层在装配碰撞、在轨微动过程中产生的微裂纹无法自行愈合,裂纹会不断扩展,不仅加剧MoS2的氧化,最终导致涂层失效,进而引发紧固件卡滞、磨损,严重威胁航天器长期运行安全

Benefits of technology

(1)润滑性能长效稳定:以纳米二硫化钼为核心润滑相,通过具有多巴胺结构的树脂从根源上阻止MoO3生成,可有效减少钛合金紧固件的粘着磨损和微动磨损,适配长期太空润滑需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978792A_ABST
    Figure CN122978792A_ABST
Patent Text Reader

Abstract

The application discloses a titanium alloy fastener self-repairing nano molybdenum disulfide lubricating coating and a preparation method thereof. The coating comprises the following components and has the following mass ratio: 50%-65% of nano molybdenum disulfide, 10%-20% of dopamine structure polymer resin, 5%-20% of polyimide, 5%-10% of antioxidant and 10%-30% of organic solvent. The dopamine structure resin is synthesized as a bonding and antioxidant core component, so that the oxidation of MoS2 to MoO3 is prevented from the root, and excellent lubricating performance, long-term chemical stability and reliable self-repairing performance of the coating are realized, and the problems of MoO3 without lubricating performance, lubricating failure, easy damage of the coating and oxidation degradation of the traditional nano molybdenum disulfide coating in long-term space service under extreme environment are solved. According to the application, the service life of the fastener can be significantly prolonged, the stability of the lubricating coating is improved, the functional requirements of the fastener in the harsh service environment are met, and long-term reliable service of the titanium alloy fastener is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of surface lubrication self-repair of titanium fasteners, and in particular to a self-repairing nano-molybdenum disulfide lubricating coating for titanium alloy fasteners and its preparation method. Background Technology

[0002] Titanium alloy fasteners are widely used in aerospace structural connections due to their excellent specific strength, corrosion resistance, and lightweight properties. However, the inherent surface properties of titanium alloys result in a high coefficient of friction, making them prone to adhesive wear and fretting wear. In long-term service environments, fasteners must withstand frequent assembly, disassembly, and vibration, necessitating a reliable surface lubrication coating to provide long-term protection.

[0003] Nano-molybdenum disulfide (MoS2), a classic solid lubricant, possesses a layered crystal structure where the S-Mo-S layers are bonded by weak van der Waals forces, resulting in extremely low shear strength and a low coefficient of friction in a vacuum environment, making it an ideal material for fastener lubrication in space environments. However, traditional nano-molybdenum disulfide coatings suffer from three major defects, failing to meet the requirements of long-term service in extreme environments: First, insufficient interfacial bonding; a dense TiO2 passivation layer easily forms on titanium alloy surfaces, leading to low bonding energy between the traditional coating and the substrate, making it prone to peeling and detachment under shear stress. Second, poor chemical stability; atomic oxygen, ultraviolet radiation, and high / low temperature cycling in the extreme space environment accelerate the oxidation and degradation of MoS2, generating non-lubricating MoO3 products in humid environments, which is a key reason for long-term lubrication failure of the coating. Third, lack of self-healing ability; microcracks generated during assembly collisions and on-orbit micro-movements cannot heal themselves, and the cracks continue to expand, not only exacerbating the oxidation of MoS2 but also ultimately leading to coating failure, which in turn causes fastener jamming and wear, seriously threatening the long-term operational safety of spacecraft.

[0004] In existing technologies, although there are modification schemes for nano-molybdenum disulfide coatings, such as adding binders to improve adhesion and introducing antioxidants to improve stability, none of them fundamentally solve the problem of MoO3 formation, and none of them simultaneously achieve synergistic optimization of lubrication performance, chemical stability and self-healing performance, making it difficult to adapt to long-term extreme working conditions. Summary of the Invention

[0005] This invention provides a self-healing nano-molybdenum disulfide lubricating coating for titanium alloy fasteners and its preparation method. By synthesizing a resin with a dopamine structure as the core component for bonding and anti-oxidation, the oxidation of MoS2 to MoO3 is prevented at the source. Simultaneously, the coating achieves excellent lubrication performance, long-term chemical stability, and reliable self-healing properties, solving the problems of traditional nano-molybdenum disulfide coatings generating non-lubricating MoO3, lubrication failure, easy coating damage, and oxidative degradation during long-term space service under extreme environments. This invention can significantly extend the service life of fasteners, improve the stability of the lubricating coating, adapt to the functional requirements of harsh service environments, and ensure the long-term reliable service of titanium alloy fasteners.

[0006] In the first aspect, a self-healing nano-molybdenum disulfide lubricating coating for titanium alloy fasteners is provided, comprising the following components and mass ratios: 50%-65% nano-molybdenum disulfide, 10%-20% dopamine structured polymer resin, 5%-20% polyimide, 5%-10% antioxidant, and 10%-30% organic solvent.

[0007] In conjunction with the first aspect, in certain implementations of the first aspect, the dopamine-structured polymer resin includes at least one of the following: polydopamine methacrylamide, poly(dopamine methacrylamide-n-butyl acrylate) binary copolymer, and poly(dopamine methacrylamide-n-butyl acrylate-n-butyl methacrylate) terpolymer.

[0008] In conjunction with the first aspect, in certain implementations of the first aspect, the dopamine-structured polymer resin satisfies any one of the following A) to D): A) Dopamine-structured polymer resins are obtained through polymerization reactions related to dopamine methacrylamide. The synthesis method of dopamine methacrylamide is as follows: 3.7g~7.4g of dopamine hydrochloride is dissolved in water, then 14.3g~28.6g of borax decahydrate is added and stirred uniformly under nitrogen protection at 0℃. Then, 2.5ml~5ml of methacryloyl chloride is gradually added dropwise using a constant pressure funnel. After reacting for 2 hours, the reaction is stopped, and the pH value is adjusted to above 9.5 using Na2CO3. Then, the pH value is adjusted to 2 using acetic acid, and the product is extracted with ethyl acetate. The organic phase is collected, dried over anhydrous MgSO4, and the solvent is removed to obtain the crude product. The crude product is recrystallized in ethyl acetate at -20℃ and dried to obtain dopamine methacrylamide. ; B) The synthesis method of polydopamine methacrylamide is as follows: Under N2 protection, dopamine methacrylamide monomer is added to a polymerization bottle, dissolved in N,N-dimethylformamide, and 1~3wt% of initiator benzoyl peroxide is added. Then the polymerization bottle is placed in a constant temperature pot at 55-75℃ for polymerization reaction for 24h. The mixture obtained from the reaction is washed several times with cyclohexane precipitation and dried in a vacuum drying oven at 55℃ to obtain polydopamine methacrylamide. C) The synthesis method of poly(dopamine methacrylamide-n-butyl acrylate) binary copolymer is as follows: Under N2 protection, n-butyl acrylate and dopamine methacrylamide monomers are added to a polymerization bottle, dissolved in N,N-dimethylformamide, and 1-3 wt% of initiator benzoyl peroxide is added. Then, the polymerization bottle is placed in a constant temperature pot at 55-75℃ for polymerization reaction for 24 hours. The resulting mixture is washed several times with cyclohexane precipitation and dried in a vacuum drying oven at 55℃ to obtain a binary copolymer of n-butyl acrylate and dopamine methacrylamide; wherein, the molar ratio of n-butyl acrylate and dopamine methacrylamide monomers is 3-6:1-2; D) The synthesis method of poly(dopamine methacrylamide-n-butyl acrylate-n-butyl methacrylate) terpolymer is as follows: Under N2 protection, n-butyl acrylate, n-butyl methacrylate, and dopamine methacrylamide monomers are added to a polymerization bottle, dissolved in N,N-dimethylformamide, and 1-3 wt% of initiator benzoyl peroxide is added. Then, the polymerization bottle is placed in a constant temperature pot at 55-75℃ for polymerization reaction for 24 hours. The resulting mixture is washed several times with cyclohexane precipitation and dried in a vacuum drying oven at 55℃ to obtain a terpolymer of n-butyl acrylate, n-butyl methacrylate, and dopamine methacrylamide; wherein, the molar ratio of the three monomers n-butyl acrylate, n-butyl methacrylate, and dopamine methacrylamide is 3-6:2-6:1-2.

[0009] In conjunction with the first aspect, in some implementations of the first aspect, the particle size of molybdenum disulfide nanoparticles is 20nm-500nm.

[0010] In conjunction with the first aspect, in some implementations of the first aspect, the antioxidant is a fluorinated polyarylether sulfone.

[0011] In conjunction with the first aspect, in some implementations of the first aspect, the organic solvent is an aqueous solution containing at least one of the following substances: chloroform, dichloromethane, dimethyl sulfoxide, or N,N-dimethylformamide; the volume percentage of the organic solvent is 65%-75%.

[0012] In conjunction with the first aspect, in some implementations of the first aspect, the thickness of the self-healing lubricating coating is 5 μm - 15 μm.

[0013] Secondly, a method for preparing a self-healing nano-molybdenum disulfide lubricating coating for titanium alloy fasteners as described in any of the implementations of the first aspect above is provided, comprising: Step 1, titanium alloy fastener pretreatment, including: mechanical polishing, ultrasonic cleaning, acid pickling and activation, and drying of the titanium alloy fastener surface; Step 2, preparation of the transition layer, includes: mixing Ni-Al alloy powder with silane coupling agent KH570 to form a transition layer spraying material, and using a spraying equipment to spray the transition layer onto the surface of the pretreated titanium alloy fastener. Step 3, preparation of self-healing lubricating layer, including: adding nano molybdenum disulfide, dopamine structured polymer resin, polyimide, antioxidant and organic solvent according to the mass ratio to obtain self-healing lubricating slurry, and coating the self-healing lubricating slurry onto the surface of the transition layer by dip coating method; Step 4, post-processing, includes: drying the coated titanium alloy fasteners in an oven; then placing them in a tube furnace for cross-linking and curing, so that the dopamine-structured polymer resin cross-links with the nano-molybdenum disulfide sheet, polyimide, and fluorinated polyarylether sulfone, ultimately forming a dense and uniform self-healing nano-molybdenum disulfide lubricating coating.

[0014] In conjunction with the second aspect, in some implementations of the second aspect, step 3 satisfies: Nano-molybdenum disulfide was added to a solvent with a volume percentage of 65%-75%, ultrasonically dispersed, stirred at 300-600 rpm for 1-2 hours, and ultrasonically treated at 200-400W for 20-40 minutes under ice-water bath conditions to obtain a uniformly dispersed nano-molybdenum disulfide dispersion. Subsequently, a synthesized dopamine-structured polymer resin, polyimide, and fluorinated polyarylene sulfone were added, stirred evenly, and then ultrasonically degassed to obtain a self-healing lubricating slurry. The self-healing lubricating slurry was coated onto the surface of the transition layer using a dip-coating method, with the dip-coating speed controlled at 100-200 mm / min, the immersion time at 10-30 s, and the lifting speed at 50-100 mm / min to reduce surface marks.

[0015] In conjunction with the second aspect, in some implementations of the second aspect, step 4 satisfies: The coated titanium alloy fasteners are dried in an oven at 75-85℃ for 20-50 minutes to remove moisture; then they are placed in a tube furnace and a protective gas of Ar:H2 with a volume ratio of 18-20:1 is introduced. The temperature is raised to 300-350℃ at a rate of 4-6℃ / min and held for 0.5-1.2 hours to carry out cross-linking and curing.

[0016] Compared with the prior art, the solution provided by the present invention has at least the following beneficial technical effects: (1) Long-term stable lubrication performance: With nano molybdenum disulfide as the core lubricating phase, the resin with dopamine structure prevents the formation of MoO3 from the source, which can effectively reduce the adhesive wear and fretting wear of titanium alloy fasteners and meet the long-term lubrication requirements of space.

[0017] (2) Excellent chemical stability: Through the synergistic protection of the resin with dopamine structure (antioxidant effect of catechol group + extreme environment resistance of fluorine segment) and Ni-Al transition layer, the coating has excellent antigenic oxygen and UV radiation resistance, which can effectively isolate the oxidizing medium and prevent the oxidation and degradation of MoS2; it does not peel off or degrade in the high and low temperature cycle (-150℃~+120℃) environment of space, and can withstand the erosion of the extreme environment of space for a long time, solving the core problem of traditional coatings being easily oxidized to form MoO3 and unstable in long-term service.

[0018] (3) Reliable self-healing performance: Through the synergistic design of the resin with dopamine structure, the coating can self-heal in room temperature and vacuum environment after microcracks are generated, with a healing efficiency of ≥90%. After healing, the coefficient of friction and mechanical properties of the coating can be restored to more than 92% of the original state, effectively inhibiting the oxidation aggravation problem caused by crack propagation, extending the long-term service life of the coating, and avoiding fastener failure caused by coating damage.

[0019] (4) Strong interface bonding: The micro-nano structure is constructed by acid washing and activation of the titanium alloy substrate. Combined with the bridging effect of silane coupling agent, the transition effect of Ni-Al transition layer, and the strong adhesion characteristics of resin with dopamine structure (the catechol group of dopamine can form a stable bond with the titanium alloy surface), the bonding strength between the coating and the titanium alloy substrate is strong, far exceeding the bonding strength standard of traditional coatings. It can withstand the shear stress of spacecraft assembly, disassembly and on-orbit micro-movement, and avoid coating peeling and falling off.

[0020] (5) Strong process adaptability: The preparation process is simple, the synthesis process of dopamine structure resin is mild and controllable, and it can be adapted to titanium alloy fasteners of different specifications and complex shapes. The process temperature is low, avoiding thermal damage to the titanium alloy matrix. It is suitable for large-scale production and can be widely used in the surface modification of titanium alloy fasteners of various spacecraft to meet the requirements of long-term space service. Attached Figure Description

[0021] Figure 1 The image shows the 1H NMR spectrum of dopamine methacrylamide prepared in Example 1.

[0022] Figure 2 The image shows the proton NMR spectrum of the ternary copolymer obtained in Example 1. Detailed Implementation

[0023] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.

[0024] This invention provides a self-healing nano-molybdenum disulfide lubricating coating for titanium alloy fasteners, comprising the following components and mass ratios: 50%-65% nano-molybdenum disulfide, 10%-20% dopamine-structured polymer resin, 5%-20% polyimide, 5%-10% antioxidant, and 10%-30% organic solvent.

[0025] The dopamine-structured polymer resin is a resin with a dopamine structure. Dopamine molecules contain catechol structures and ethylamine groups. Its polymers exhibit excellent adhesion, antioxidant properties, and cross-linking ability. Furthermore, the catechol groups have a strong coordination effect on metals, effectively inhibiting the formation of metal oxides. The core improvement of this invention lies in introducing a resin with a dopamine structure into a self-healing lubricating layer. The catechol groups in the dopamine-structured resin can form a stable coordination with MoS2, inhibiting the oxidation of Mo atoms and preventing the formation of MoO3 at its source. Simultaneously, the self-polymerization and cross-linking characteristics of the dopamine structure endow the coating with self-healing properties and interfacial bonding strength, enabling the lubricating coating to possess excellent lubrication performance, high chemical stability, and self-repairing function. Moreover, the nano-molybdenum disulfide coating bonds firmly to the titanium alloy substrate, becoming a key solution to the long-term lubrication problem of titanium alloy fasteners in spacecraft.

[0026] In this invention, preferably, the particle size of the nano-molybdenum disulfide is 20nm-500nm.

[0027] In this invention, the antioxidant is preferably a fluorinated polyarylether sulfone.

[0028] In this invention, preferably, the organic solvent is an aqueous solution containing at least one of the following substances: chloroform, dichloromethane, dimethyl sulfoxide, or N,N-dimethylformamide (DMF). Preferably, the volume percentage of the organic solvent is 65%-75%.

[0029] In this invention, preferably, the dopamine-structured polymer resin includes at least one of the following: polydopamine methacrylamide, poly(dopamine methacrylamide-n-butyl acrylate) binary copolymer, and poly(dopamine methacrylamide-n-butyl acrylate-n-butyl methacrylate) terpolymer.

[0030] In this invention, preferably, the dopamine-structured polymer resin is obtained through a polymerization reaction related to dopamine methacrylamide. The synthesis method of dopamine methacrylamide is as follows: 3.7g~7.4g of dopamine hydrochloride is dissolved in water, then 14.3g~28.6g of borax decahydrate is added and stirred uniformly under nitrogen protection at 0°C. Then, 2.5ml~5ml of methacryloyl chloride is gradually added dropwise using a constant pressure funnel. After reacting for 2 hours, the reaction is stopped, and the pH is adjusted to above 9.5 using Na2CO3. Then, the pH is adjusted to 2 using acetic acid, and the mixture is extracted with ethyl acetate. The organic phase is collected, dried over anhydrous MgSO4, and the solvent is removed to obtain the crude product. This crude product is recrystallized in ethyl acetate at -20°C and dried to obtain dopamine methacrylamide.

[0031] In this invention, preferably, the dopamine-structured polymer resin may include polydopamine methacrylamide, which is synthesized as follows: Under N2 protection, dopamine methacrylamide monomer is added to a polymerization bottle, and 1-3 wt% of benzoyl peroxide (BPO) initiator is added with DMF. Then, the polymerization bottle is placed in a constant temperature pot at 55-75°C for polymerization reaction for 24 hours. The resulting mixture is washed several times with cyclohexane precipitation and dried in a vacuum drying oven at 55°C to obtain polydopamine methacrylamide.

[0032] In this invention, preferably, the dopamine-structured polymer resin may include a poly(dopamine methacrylamide-n-butyl acrylate) binary copolymer, the synthesis method of which is as follows: under N2 protection, n-butyl acrylate and dopamine methacrylamide monomers are added to a polymerization bottle, dissolved in DMF, and 1-3 wt% of initiator BPO is added. Then, the polymerization bottle is placed in a constant temperature pot at 55-75°C for polymerization reaction for 24 hours. The resulting mixture is washed several times with cyclohexane precipitation and dried in a vacuum drying oven at 55°C to obtain a binary copolymer of n-butyl acrylate and dopamine methacrylamide; wherein, the molar ratio of n-butyl acrylate and dopamine methacrylamide monomers is 3-6:1-2.

[0033] In this invention, preferably, the dopamine-structured polymer resin may include a poly(dopamine methacrylamide-n-butyl acrylate-n-butyl methacrylate) terpolymer, the synthesis method of which is as follows: under N2 protection, n-butyl acrylate, n-butyl methacrylate, and dopamine methacrylamide monomers are added to a polymerization bottle, dissolved in DMF, and 1-3 wt% of initiator BPO is added. Then, the polymerization bottle is placed in a constant temperature pot at 55-75°C for polymerization reaction for 24 hours. The resulting mixture is washed several times with cyclohexane precipitation and dried in a vacuum drying oven at 55°C to obtain a terpolymer of n-butyl acrylate, n-butyl methacrylate, and dopamine methacrylamide; wherein, the molar ratio of the three monomers n-butyl acrylate, n-butyl methacrylate, and dopamine methacrylamide is 3-6:2-6:1-2.

[0034] The present invention also provides a method for preparing a self-healing nano-molybdenum disulfide lubricating coating for titanium alloy fasteners, which specifically includes the following steps.

[0035] Step 1: Pretreatment of titanium alloy matrix.

[0036] First, the surface of the titanium alloy fastener is mechanically polished to control the surface roughness to Ra=0.05-0.1μm. Then, it is ultrasonically cleaned with acetone, ethanol and deionized water for 10-20 minutes in sequence to remove surface oil and impurities. Subsequently, it is immersed in a mixed acid solution with HF concentration of 6-10wt% and HNO3 concentration of 22-28wt% for 1-3 minutes for acid washing and activation. After being dried with nitrogen, it is placed in a vacuum drying oven at 55-65℃ for 0.5-1.2 hours to obtain the activated substrate surface, construct a micro-nano-level rough structure, and enhance the mechanical anchoring effect of the coating.

[0037] Step 2, preparation of the transition layer.

[0038] A transition layer is formed by thoroughly mixing Ni-Al alloy powder with silane coupling agent KH570. The transition layer is then sprayed onto the pretreated titanium alloy substrate using a spraying device. The spraying temperature is controlled at 800-1000℃, the spraying pressure at 0.3-0.5MPa, and the spraying distance at 150-200mm to ensure that the transition layer is uniform, dense, and firmly bonded to the substrate.

[0039] Step 3, preparation of self-healing lubricating layer.

[0040] Using nano-molybdenum disulfide as the core lubricating phase and the aforementioned dopamine-structured polymer resin as the matrix binder phase, polyimide, antioxidants, and organic solvents are added according to the mass ratio. Specifically, firstly, a nano-molybdenum disulfide dispersion is prepared by adding nano-molybdenum disulfide to a solvent with a volume percentage of 65%-75%, ultrasonically dispersing it, stirring at 300-600 rpm for 1-2 hours, and then ultrasonically treating it at 200-400W for 20-40 minutes under ice-water bath conditions to obtain a uniformly dispersed nano-molybdenum disulfide dispersion; subsequently, the synthesized dopamine-structured polymer resin, polyimide, and fluorinated polyarylether sulfone are added, stirred evenly, and then ultrasonically degassed to obtain a self-healing lubricating slurry; the self-healing lubricating slurry is coated onto the surface of the transition layer using a dip-coating method, controlling the dip speed at 100-200 mm / min, the soaking time at 10-30 s, and the pull-out speed at 50-100 mm / min to reduce surface marks.

[0041] Step 4, post-processing.

[0042] The coated titanium alloy fasteners are dried in an oven at 75-85℃ for 20-50 minutes to remove moisture. They are then placed in a tube furnace, and a protective gas mixture of Ar:H2 (volume ratio 18-20:1) is introduced. The temperature is increased to 300-350℃ at a rate of 4-6℃ / min and held for 0.5-1.2 hours for cross-linking and curing. This process cross-links the dopamine-structured polymer resin with the nano-molybdenum disulfide sheets, polyimide, and fluorinated polyarylether sulfone, ultimately forming a dense and uniform self-healing nano-molybdenum disulfide lubricating coating. Preferably, the thickness of the self-healing lubricating coating is controlled to be 5μm-15μm.

[0043] The present invention will be further described below with reference to specific embodiments, and the advantages and features of the present invention will become clearer with the description. However, the embodiments are merely exemplary and do not constitute any limitation on the scope of the present invention. Those skilled in the art should understand that modifications or substitutions can be made to the details and form of the technical solutions of the present invention without departing from the spirit and scope of the present invention, but all such modifications and substitutions fall within the protection scope of the present invention.

[0044] Example 1: Preparation of a self-healing nano-molybdenum disulfide lubricating coating for titanium alloy fasteners 1) Preparation of dopamine methacrylamide 7.4 g (38.9 mmol) of dopamine hydrochloride was dissolved in 250 ml of water, and then 28.6 g (78 mmol) of borax decahydrate (Na₂B₄O₇·10H₂O) was added. The mixture was stirred uniformly under nitrogen protection at 0 °C. Then, 5 ml (46.5 mmol) of methacryloyl chloride was gradually added dropwise over 5 min using a constant pressure funnel. After 2 hours, the reaction was stopped, and the pH was adjusted to above 9.5 using Na₂CO₃. The pH was then adjusted to 2 using acetic acid, and the mixture was extracted with ethyl acetate. The organic phase was collected, dried over anhydrous MgSO₄, and the solvent was removed to obtain the crude product. This crude product was recrystallized from ethyl acetate at -20 °C and dried to obtain a refined dopamine methacrylamide product with a yield of approximately 45%. Figure 1 The image shows the 1H NMR spectrum of dopamine methacrylamide prepared in Example 1.

[0045] 2) Synthesis of terpolymers Under N2 protection, 1.28 g (10 mmol) of n-butyl acrylate, 1.41 g (10 mmol) of n-butyl methacrylate, and 0.44 g (2 mmol) of dopamine methacrylamide (the molar ratio of the three monomers is 5:5:1) were weighed and added to a polymerization flask. The mixture was dissolved in 15 g of N,N-dimethylformamide, and 1 wt% (0.183 g) of azobisisobutyronitrile (AIBN) was added as an initiator. The polymerization flask was then placed in a 60°C constant temperature reactor and reacted for 24 h. The resulting mixture was washed three times with cyclohexane precipitation and dried in a vacuum drying oven at 55°C. The 1H NMR spectrum of the obtained terpolymer is shown below. Figure 2 As shown.

[0046] 3) Preparation of self-healing lubricating layer for titanium alloy fasteners 50g of molybdenum disulfide with a particle size of 100nm was added to 10g of dichloromethane solvent, ultrasonically dispersed, stirred at 500rpm for 1.5h, and ultrasonically treated at 300W for 30min under ice-water bath conditions to obtain a uniformly dispersed molybdenum disulfide dispersion. 10g of the dopamine-structured terpolymer synthesized in step 2), 10g of polyimide, 7g of the antioxidant fluorinated polyarylene sulfone, and 10g of dichloromethane were taken, stirred evenly, and then ultrasonically degassed. The slurry was coated onto the surface of the titanium alloy fastener with a transition layer using a dip-coating method. The dip-coating speed was controlled at 150mm / min, the immersion time at 20s, and the pull-out speed at 100mm / min to reduce surface marks. The coated titanium alloy fasteners were dried in an oven at 75-85℃ for 40 minutes to remove moisture. Then they were placed in a tube furnace and a protective gas of Ar / H2 with a volume ratio of 20:1 was introduced. The temperature was increased to 300-350℃ at a rate of 4-6℃ / min and held for 1 hour to carry out cross-linking and curing. This process allowed the resin with the dopamine structure to cross-link with the nano molybdenum disulfide sheet, polyimide, and fluorinated polyarylether sulfone, ultimately forming a dense and uniform self-healing molybdenum disulfide lubricating coating.

[0047] The coating samples 1# and 2# prepared in this embodiment were used. One sample 1# was scratched with a blade to make a micro-scratch on the coating, while the other sample 2# was not scratched. The two samples were then placed at room temperature for 3 days for observation. It was found that the micro-scratch on the samples became smaller.

[0048] Example 2: Preparation of a self-healing nano-molybdenum disulfide lubricating coating for titanium alloy fasteners 1) Prepare dopamine methacrylamide functional monomers according to the same method as in Example 1, for later use.

[0049] 2) Preparation of n-butyl acrylate, n-butyl methacrylate, and dopamine-methacrylamide terpolymer Under nitrogen protection, 1.28 g (10 mmol) of n-butyl acrylate, 1.41 g (10 mmol) of n-butyl methacrylate, and 0.88 g (4 mmol) of dopamine methacrylamide (the molar ratio of the three monomers is 5:5:2) were weighed and added to a polymerization flask, dissolved in 15 g of dimethyl sulfoxide, and 1 wt% (0.186 g) of dimethyl azobisisobutyrate was added as an initiator. The polymerization flask was then placed in a 60°C constant temperature reactor and reacted for 24 h. The resulting mixture was washed three times with cyclohexane precipitation and dried in a vacuum drying oven at 55°C.

[0050] 3) Prepare a self-healing lubricating coating for titanium alloy fasteners using the same method as in Example 1, and set aside for later use. Apply the coating to the surface of the titanium alloy fastener with the transition layer using the method in Example 1.

[0051] The coating samples 3# and 4# prepared in this embodiment were used. One sample 3# was scratched with a blade to create a micro-scratch on the coating, while the other sample 4# was not scratched. The two samples were then placed at room temperature for 3 days for observation. It was found that the micro-scratch on the samples became smaller.

[0052] Comparative Example 3: Commercially available nano-molybdenum disulfide lubricating coating Purchase commercially available nano-molybdenum disulfide lubricating coating and apply it to the surface of the titanium alloy fastener with a transition layer using the same dip-coating method. Take coating samples 5# and 6# obtained in this embodiment, and make a scratch on sample 5# with a blade. Then, place samples 5# and 6# at room temperature and observe the changes using an optical microscope for comparison.

[0053] Table 1 Comparison of the performance of the prepared self-healing nano-molybdenum disulfide lubricating coating for titanium alloy fasteners with commercially available products.

[0054] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope defined in the claims of the present invention.

Claims

1. A self-healing nano-molybdenum disulfide lubricating coating for titanium alloy fasteners, characterized in that, The components and their weight ratios are as follows: 50%-65% nano molybdenum disulfide, 10%-20% dopamine structured polymer resin, 5%-20% polyimide, 5%-10% antioxidant, and 10%-30% organic solvent.

2. The coating according to claim 1, characterized in that, The dopamine-structured polymer resin includes at least one of the following: polydopamine methacrylamide, poly(dopamine methacrylamide-n-butyl acrylate) binary copolymer, and poly(dopamine methacrylamide-n-butyl acrylate-n-butyl methacrylate) terpolymer.

3. The coating according to claim 2, characterized in that, Dopamine-structured polymer resins satisfy any one of the following A) to D): A) Dopamine-structured polymer resins are obtained through polymerization reactions related to dopamine methacrylamide. The synthesis method of dopamine methacrylamide is as follows: 3.7g~7.4g of dopamine hydrochloride is dissolved in water, then 14.3g~28.6g of borax decahydrate is added and stirred uniformly under nitrogen protection at 0℃. Then, 2.5ml~5ml of methacryloyl chloride is gradually added dropwise using a constant pressure funnel. After reacting for 2 hours, the reaction is stopped, and the pH value is adjusted to above 9.5 using Na2CO3. Then, the pH value is adjusted to 2 using acetic acid, and the product is extracted with ethyl acetate. The organic phase is collected, dried over anhydrous MgSO4, and the solvent is removed to obtain the crude product. The crude product is recrystallized in ethyl acetate at -20℃ and dried to obtain dopamine methacrylamide. ; B) The synthesis method of polydopamine methacrylamide is as follows: Under N2 protection, dopamine methacrylamide monomer is added to a polymerization bottle, dissolved in N,N-dimethylformamide, and 1~3wt% of initiator benzoyl peroxide is added. Then the polymerization bottle is placed in a constant temperature pot at 55-75℃ for polymerization reaction for 24h. The mixture obtained from the reaction is washed several times with cyclohexane precipitation and dried in a vacuum drying oven at 55℃ to obtain polydopamine methacrylamide. C) The synthesis method of poly(dopamine methacrylamide-n-butyl acrylate) binary copolymer is as follows: Under N2 protection, n-butyl acrylate and dopamine methacrylamide monomers are added to a polymerization bottle, dissolved in N,N-dimethylformamide, and 1-3 wt% of initiator benzoyl peroxide is added. Then, the polymerization bottle is placed in a constant temperature pot at 55-75℃ for polymerization reaction for 24 hours. The resulting mixture is washed several times with cyclohexane precipitation and dried in a vacuum drying oven at 55℃ to obtain a binary copolymer of n-butyl acrylate and dopamine methacrylamide; wherein, the molar ratio of n-butyl acrylate and dopamine methacrylamide monomers is 3-6:1-2; D) The synthesis method of poly(dopamine methacrylamide-n-butyl acrylate-n-butyl methacrylate) terpolymer is as follows: Under N2 protection, n-butyl acrylate, n-butyl methacrylate, and dopamine methacrylamide monomers are added to a polymerization bottle, dissolved in N,N-dimethylformamide, and 1-3 wt% of initiator benzoyl peroxide is added. Then, the polymerization bottle is placed in a constant temperature pot at 55-75℃ for polymerization reaction for 24 hours. The resulting mixture is washed several times with cyclohexane precipitation and dried in a vacuum drying oven at 55℃ to obtain a terpolymer of n-butyl acrylate, n-butyl methacrylate, and dopamine methacrylamide; wherein, the molar ratio of the three monomers n-butyl acrylate, n-butyl methacrylate, and dopamine methacrylamide is 3-6:2-6:1-2.

4. The coating according to claim 1, characterized in that, The particle size of the nano-molybdenum disulfide is 20nm-500nm.

5. The coating according to claim 1, characterized in that, The antioxidant is a fluorinated polyarylether sulfone.

6. The coating according to claim 1, characterized in that, The organic solvent is: chloroform, dichloromethane, dimethyl sulfoxide or N,N-dimethylformamide.

7. The coating according to claim 1, characterized in that, The thickness of the self-healing lubricating coating is 5μm-15μm.

8. A method for preparing a self-healing nano-molybdenum disulfide lubricating coating for titanium alloy fasteners as described in any one of claims 1 to 7, characterized in that, include: Step 1, titanium alloy fastener pretreatment, including: mechanical polishing, ultrasonic cleaning, acid pickling and activation, and drying of the titanium alloy fastener surface; Step 2, preparation of the transition layer, includes: mixing Ni-Al alloy powder with silane coupling agent KH570 to form a transition layer spraying material, and using a spraying equipment to spray the transition layer onto the surface of the pretreated titanium alloy fastener. Step 3, preparation of self-healing lubricating layer, including: adding nano molybdenum disulfide, dopamine structured polymer resin, polyimide, antioxidant and organic solvent according to the mass ratio to obtain self-healing lubricating slurry, and coating the self-healing lubricating slurry onto the surface of the transition layer by dip coating method; Step 4, post-processing, includes: drying the coated titanium alloy fasteners in an oven; then placing them in a tube furnace for cross-linking and curing, so that the dopamine-structured polymer resin cross-links with the nano-molybdenum disulfide sheet, polyimide, and fluorinated polyarylether sulfone, ultimately forming a dense and uniform self-healing nano-molybdenum disulfide lubricating coating.

9. The preparation method according to claim 8, characterized in that, Step 3 satisfies: Nano-molybdenum disulfide was added to a solvent with a volume percentage of 65%-75%, ultrasonically dispersed, stirred at 300-600 rpm for 1-2 hours, and ultrasonically treated at 200-400W for 20-40 minutes under ice-water bath conditions to obtain a uniformly dispersed nano-molybdenum disulfide dispersion. Subsequently, a synthesized dopamine-structured polymer resin, polyimide, and fluorinated polyarylene sulfone were added, stirred evenly, and then ultrasonically degassed to obtain a self-healing lubricating slurry. The self-healing lubricating slurry was coated onto the surface of the transition layer using a dip-coating method, with the dip-coating speed controlled at 100-200 mm / min, the immersion time at 10-30 s, and the lifting speed at 50-100 mm / min to reduce surface marks.

10. The preparation method according to claim 8, characterized in that, Step 4 satisfies: The coated titanium alloy fasteners are dried in an oven at 75-85℃ for 20-50 minutes to remove moisture; then they are placed in a tube furnace and a protective gas of Ar:H2 with a volume ratio of 18-20:1 is introduced. The temperature is raised to 300-350℃ at a rate of 4-6℃ / min and held for 0.5-1.2 hours to carry out cross-linking and curing.